Schematic Design of Planetary Gear Transmission for Automatic Transmission Based on Graph Theory - Huiling Xue; Lijian Li; Fei Guo (Jixie chuandong)
The topological graph of planetary gear mechanism is established. Some topological graphs of two and three DOF planetary gear mechanism are synthesized. The procedures of isomorphism identification and rigid subchain detection are particularly presented. According to the transformation rules， topological graphs of planetary gear mechanism are converted into standard topological graphs and kinematic diagrams. Some transmission schemes of two planetary rows and three planetary rows are obtained.